Increasing the Adaptive Capacity of the Organism When Exposed to Adverse Environmental Factors Through Phytoadaptogens; IOP Conference Series: Materials Science and Engineering; Vol. 221 : Innovative Technologies in Engineering - Babii N. V.; Pomozova V. A.; Kiseleva T. F.; Romanenko V. O. Vasily Olegovich (2017, 2017)
Title screen